АНАЛІТИЧНИЙ ОГЛЯД ТА ВИБІР ОПТИЧНИХ ЛАЗЕРНИХ СИСТЕМ ДЛЯ ВИМІРЮВАННЯ ПОВІТРЯНИХ ЗАЗОРІВ У ПОТУЖНИХ ГІДРОГЕНЕРАТОРАХ - Брагинець, І.О.; Кононенко, О.Г.; Масюренко, Ю.О. (Інститут електродинаміки Національної академії наук України, 2018)
The work analyzes the known optical laser systems (OLS) for measuring linear dimensions and displacements of objects, including rotating objects or heated to high temperatures. The purpose of the studies is to assess the possibility of using these OLS for determining the air gaps of powerful hydrogenerators. The factors that were taken into account when considering such systems are indicated. The features of hydrogenerators design and the requirements for the accuracy and time of a single measurement of the air gap are noted. The main methods of the distance measuring on which the OLS is based are considered, and the advantages and disadvantages of each of them are determined in the practical implementation of the systems. Taking into account the design of the hydrogenerator and the conditions of its operation, it is indicated on the expediency of using fiber-optic lines for the transmission and reception of laser radiation. The recommendations on the application of the OLS, based on the results of the research, were developed. References 12, figure 6.